Przebieg odbudowy kaliskiej kamienicy po zniszczeniach I Wojny Światowej - Rabiega, Mateusz (Wydawnictwo Politechniki Łódzkiej, 2021)
Przeprowadzenie analizy dokumentacji archiwalnej i stanu obecnego wybranych kaliskich kamienic pozwala podjąć próbę opisania procesu prowadzącego do odbudowy kaliskiej kamienicy po zniszczeniach i wojny światowej.

The analysis of the archival documentation and the current state of selected tenement houses in Kalisz allows for an attempt to describe the process leading to the rebuilding of the tenement house in Kalisz after the destruction of World War I.
The process of rebuilding a tenement house in Kalisz after the destruction of World War I
Keywords: Kalisz; kamienica; odbudowa; dwudziestolecie międzywojenne; Kalisz; tenement house; reconstruction; interwar period